Analysis of chaotic methods for compression and encryption processes in data communication - Özkaynak, Fatih; Özer, A. Bedri; Yavuz, Sirma (My University, 2012)
Data compression and encryption are critical issues for efficiency and security requirements of information transmission. In order to improve the performance and the flexibility of multimedia applications, it is worthwhile to perform compression and encryption in a single process. Recently Hermassi et al. proposed a method for joint compression and encryption using chaotically mutated Huffman trees. The proposed method based on multiple Huffman tables simultaneously performs encryption and compression by a key-controlled swapping of the left and right branches of the Huffman tree. However, security problems were found. In this study describes the security weakness of the proposed method. By applying chosen-plaintext attacks, we show that secret key can be revealed. © 2012 IEEE.
Veri? i?leti?şi?mi?nde sikiştirma ve şi?freleme süreçleri? i?çi?n kaoti?k yöntemleri?n anali?zi?
2012 20th Signal Processing and Communications Applications Conference, SIU 2012 -- 18 April 2012 through 20 April 2012 -- Fethiye, Mugla -- 90786
Keywords: Algorithms; Data Processing; Forestry; Safety; Telecommunications; Cryptography; Forestry; Signal processing; Chosen-plaintext attack; Critical issues; Data-communication; Huffman tables; Huffman trees; Information transmission; Joint Compression and Encryption; Multimedia applications; Secret key; Security problems; Security requirements; Security weakness; Single process; Data compression